PENYULUHAN BUDAYA MENABUNG UNTUK ANAK SERTA MENGELOLA KEUANGAN SENDIRI SECARA MANDIRI DENGAN HEMAT, CERMAT DAN TEPAT PADA PESERTA DIDIK YAYASAN LEMBAGA AMIL ZAKAT NASIONAL MIZAN AMANAH - Ading Sunarto; Edy Krisyanto; Nindie Ellesia (Indonesian Collaboration Journal of Community Services, 2023)
The purpose of this Community Service activity is to carry out one of the Three Pillars of Higher Education and its main objective is to provide an overview of strategies that can be implemented in an effort to foster motivation to save today's students, especially for Mizan Amanah National Amil Zakat Institution Foundation Students. In addition, it is hoped that with this community service the existence of higher education institutions can make a major contribution to the development and application of science to the community. The method used for the activities carried out was that we went directly to the PKM location, namely at the Mizan Amanah National Amil Zakat Institution Foundation, which is located at Jl. Bintaro Utama 3 Blok AP No.50A, Bintaro, Pondok Aren District, South Tamgerang City, Banten 15221. The results of the community service were obtained, namely increasing the motivation of children to save more actively and increasing their motivation, especially after the Covid-19 pandemic so that they have a good perspective on the importance of improving and building self-motivation to save even better and learn to be responsible in the present as their provision for life in the future. The knowledge gained at Community Service this time is expected to be able to provide new enthusiasm for lecturers in an effort to develop themselves by providing direction, delivering material and motivation and contributing to the younger generation both within the school, campus, family and society at large.